(untitled) (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Neonatal sepsis is one of the major causes of mortality in neonates. Hypothermia is also an important contributing factor of neonatal mortality. Neonates with sepsis can present with normal temperature, hypo or hyperthermia. Objectives: This study was design to find out the pattern of temperature on admission and its association with mortality among neonates admitted with sepsis. Methods: This cross-sectional study was conducted from September 2017 to April 2018 in the Department of Neonatal Medicine and NICU, Dhaka Shishu (Children) Hospital. Neonates up to thirty days of age, diagnosed as probable sepsis were enrolled. On admission, axillary temperature was recorded for 3 minutes and neonates were categorized according to the recorded temperature. Neonates were classified as early onset sepsis (EOS) and late onset sepsis (LOS) according to the age of onset of the sepsis. Outcome was also recorded. Statistical analysis was done by SPSS program version 25. Chi-square (X2) test was done to determine the association and p value, <0.05 was taken as significant. Results: Among 493 enrolled neonates, 41.2% neonates were with early onset sepsis (EOS) and 58.8% were with late onset sepsis (LOS). Out of 493 neonates, 89(18.1%) died. Among the enrolled neonates, 54.4% had normal temperature, 16.6% had mild hypothermia, 14.6% had moderate hypothermia and 14.4% had hyperthermia. It was found that mild and moderate hypothermia were significantly more in EOS(p<0.05). Mortality was significantly high in neonates with mild and moderate hypothermia (p<0.05). Conclusion: This study found that mortality was associated with mild and moderate hypothermia in neonates admitted with sepsis. DS (Child) H J 2019; 35(2) : 150-155